Pengaruh Supervisi Akademik Pengawas Sekolah, Kepemimpinan Kepala Sekolah dan Iklim Organisasi Terhadap Kinerja Guru Sekolah Dasar Kecamatan Warunggunung Kabupaten Lebak - Siti Maesyaroh; Ila Rosmilawati; Aan Hendrayana (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze the effect of academic supervision, principal leadership, and organizational climate on teacher performance in public elementary schools in Warunggunung District, Lebak Regency. This research employed a quantitative approach with a correlational design. The population consisted of 320 teachers, and a sample of 178 teachers was selected using stratified random sampling. Data were collected through Likert-scale questionnaires that had been tested for validity and reliability. Data analysis techniques included descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing using t-test and F-test. The results showed that academic supervision, principal leadership, and organizational climate have positive and significant effects on teacher performance, both partially and simultaneously. The Spearman correlation analysis indicated strong relationships between variables, with organizational climate having the strongest correlation (0.832), followed by principal leadership (0.802) and academic supervision (0.755). The results of multiple regression analysis revealed that all independent variables significantly influence teacher performance, with a coefficient of determination (R²) of 0.671, indicating that 67.1% of the variance in teacher performance is explained by these variables. In conclusion, improving teacher performance requires an integrated approach through effective academic supervision, strong principal leadership, and a conducive organizational climate. These findings highlight the importance of school management practices in enhancing teacher performance and educational quality.